Comparison of the smiley face rod method versus intervertebral fusion for the treatment of L5 spondylolysis in adults - Dong, Qi-Yuan; Yang, Xue-Fei; Wu, Hai-Long; Shi, Yan; Yu, Li-Min; Huang, Yong-Can; Yu, Bin-Sheng (Frontiers in Medicine, 2024)
Purpose For patients who suffered from L5 spondylolysis and fail to improve using conservative treatment, the best surgical strategy remains controversial. This study compares the efficacy of the treatment of L5 spondylolysis using the smiley face rod (SFR) method versus intervertebral fusion (IF). Methods We analyzed 38 patients with L5 spondylolysis who underwent surgery in our department between January 2017 and June 2019. Of these, 32 patients were included in our study: 14 patients in the SFR group and 18 patients in the IF group. The operation time, intraoperative blood loss, postoperative drainage time, length of stay and postoperative complications were compared. The pain visual analog scale (VAS) and Oswestry dysfunction index (ODI) were evaluated before operation and at 3 months, 6 months, and 1 year postoperatively. The changes in range of motion (ROM) in L4/5 and L5/S1 in these two groups before and after surgery were measured through imaging examinations and the bone graft fusion rate was assessed according to the Brown standard. Results The operation time of the SFR group was much shorter than that of the IF group (98.8 ± 8.3 vs. 113.8 ± 8.6 min, P < 0.05), and the blood loss of the SFR group was significantly lower than that of the IF group (90.0 ± 43.9 vs. 175.0 ± 81.2 ml, P < 0.05). Length of stay in the SFR group was less than that of the IF group (9.5 ± 2.5 vs. 12.6 ± 3.2 d, P < 0.05). No difference was found in the VAS and ODI scores between the two groups at 3 months, 6 months, and 1 year after surgery. In the IF group, the ROM in L4/5 showed an obvious increase after surgery compared to that before surgery, and it was much bigger than that of the SFR group (P < 0.05). A notable reduction of ROM was seen in L5/S1 in the IF group compared to the SFR group (P < 0.05). The fusion rate of the isthmus in the SFR group was 79% at 3 months and 86% at 6 months after surgery. In the IF group, one patient suffered from adjacent segment degeneration (ASD), which caused compression symptoms in the lower extremity, and one patient suffered from an internal fixation fracture; these complications were not seen in the SFR group. Conclusion The SFR and IF both improve the clinical symptoms and quality of life of patients with L5 spondylolysis. However, the SFR technique had the advantages of a shorter operation time and less blood loss than IF; it could also preserve the ROM of the surgical segment and had little influence on adjacent segments in short-term follow-ups.